Money Politic in Elections: A Thereat to Integrity and Legality (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
Money politics in elections is one of the serious problems that threaten the quality of democracy in Indonesia. This practice not only undermines the principles of fairness and transparency in elections, but also weakens the accountability and integrity of the government system. This study aims to analyse the factors that drive money politics and its impact on democracy. The method used in this research is descriptive analysis with a qualitative approach, based on literature review and secondary data related to money politics in elections. The results show that money politics is driven by various factors, including patronage culture, weak law enforcement, low public political awareness, and economic inequality that makes people vulnerable to vote-buying practices. The impact of money politics is detrimental, including the distortion of political representation, the emergence of corrupt governments, and weak public trust in the electoral system. To overcome this problem, synergy is needed between the government, EMB, law enforcement agencies, political parties, and civil society in strengthening regulations and law enforcement. In addition, more intensive political education is needed to increase public awareness of the dangers of money politics and encourage active participation in creating clean and democratic elections.